2006
DOI: 10.1093/cercor/bhl062
|View full text |Cite
|
Sign up to set email alerts
|

Mood States Modulate Activity in Semantic Brain Areas during Emotional Word Encoding

Abstract: It is controversially discussed whether or not mood-congruent recall (i.e., superior recall for mood-congruent material) reflects memory encoding processes or reduces to processes during retrieval. We therefore investigated the neurophysiological correlates of mood-dependent memory during emotional word encoding. Event-related potentials (ERPs) were recorded while participants in good or bad mood states encoded words of positive and negative valence. Words were either complete or had to be generated from fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 51 publications
10
76
3
1
Order By: Relevance
“…Specifically, Kiefer, Schuch, Schenck, and Fiedler (2006) found that while studying positive words, those in positive relative to negative mood states evoked a smaller N400, a component sensitive to semantic incongruence. To the best our knowledge, this is the first study to show an association between negative mood and the emotion-related LPC when viewing emotional items.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, Kiefer, Schuch, Schenck, and Fiedler (2006) found that while studying positive words, those in positive relative to negative mood states evoked a smaller N400, a component sensitive to semantic incongruence. To the best our knowledge, this is the first study to show an association between negative mood and the emotion-related LPC when viewing emotional items.…”
Section: Discussionmentioning
confidence: 96%
“…Minimum norm was computed with depth weighting, spatio-temporal weighting and noise weighting for each individual channel. Cortical currents were determined within the time window during which significant ERP differences were obtained at the time point of maximal global field power (GFP) in the ERP difference waves to ensure optimal signal-to-noise-ratio (Kiefer et al, 2007a). Talairach coordinates for the activation peaks were determined on the 2D surface covering the cortex on which the source solution was computed.…”
Section: Stimuli and Procedures For The Perceptual Acoustic Task (Expementioning
confidence: 99%
“…Although the negative deflection often temporally overlaps with a large positive component (late-positive complex) and does not necessarily appear as a negative potential in absolute terms, this phenomenon is known as the N400 priming effect (Bentin, McCarthy, & Wood, 1985;Kiefer, 2005;Kiefer, Weisbrod, Kern, Maier, & Spitzer, 1998). Intracranial ERP recordings (Nobre & McCarthy, 1995) and source analyses of scalp potentials (Kiefer, Schuch, Schenck, & Fiedler, 2007) have implicated a region in the anterior-medial temporal lobe in generating the N400 ERP component.…”
Section: Introductionmentioning
confidence: 99%